Close association between abnormal expressed enzymes of energy metabolism and diarrhea-predominant irritable bowel syndrome - Chun-Yan Zhang; Xin Yao; Gang Sun; Yun-Sheng Yang; Ning-Ning Wang (Chinese Medical Journal, 2019)
Abstract. Background:. Irritable bowel syndrome (IBS) is one of the most common functional intestinal diseases, but its pathogenesis is still unknown. The present study aimed to screen the differentially expressed proteins in the mucosa of colon between IBS with diarrhea (IBS-D) patients and the healthy controls. Methods:. Forty-two IBS-D patients meeting the Rome III diagnostic criteria and 40 control subjects from July 2007 to June 2009 in Chinese PLA General Hospital were enrolled in the present study. We examined the protein expression profiles in mucosa of colon corresponding to IBS-D patients (n = 5) and controls (n = 5) using 2-dimensional gel electrophoresis (2-DE) and mass spectrometry (MS). Secondly, Western blot and immunohistochemical analysis were carried out to validate the screened proteins in 27 IBS-D patients and 27 controls. Thirdly, high-performance liquid chromatography (HPLC) was further carried out to determine ATP concentration in the mucosa of colon between 10 IBS-D patients and 8 controls. Comparisons between 2 groups were performed by Student's t-test or Mann-Whitney U-test. Results:. Twelve differentially expressed proteins were screened out. The α-enolase (ENOA) in the sigmoid colon (0.917 ± 0.007 vs. 1.310 ± 0.100, t = 2.643, P = 0.017) and caecum (0.765 ± 0.060 vs. 1.212 ± 0.122, t = 2.225, P = 0.023), Isobutyryl-CoA dehydrogenase (ACAD8) in the sigmoid colon (1.127 ± 0.201 vs. 1.497 ± 0.392, t = 7.093, P = 0.008) of the IBS-D group were significantly lower while acetyl-CoA acetyltransferase (CT) in the caecum (2.453 ± 0.422 vs. 0.931 ± 0.652, t = 8.363, P = 0.015) and ATP synthase subunit d (ATP5H) in the sigmoid (0.843 ± 0.042 vs. 0.631 ± 0.042, t = 8.613,P = 0.007) of the IBS-D group was significantly higher, compared with the controls. The ATP concentration in the mucosa of the sigmoid colon in IBS-D group was significantly lower than that of control group (0.470 [0.180, 1.360] vs. 5.350 [2.230, 7.900], U = 55, P < 0.001). Conclusions:. Many proteins related to energy metabolism presented differential expression patterns in the mucosa of colon of the IBS-D patients. The abnormalities in energy metabolism may be involved in the pathogenesis of IBS which deserves more studies to elucidate.